Legal and Ethical Discourse of Saviour Sibling: How Should Indonesia Respond to this New Trend? - Innaka, RA Antari; Jibril, Muhammad (Udayana Journal of Law and Culture; Vol 7 No 1 (2023), 2023)
Thalassemia major  is a genetic condition characterized by an inefficient synthesis of red blood cells which can be cured by bone marrow transplantation surgery. However, getting a matching donor is a challenging task. Therefore, some people have been using the “saviour sibling” procedure wherein a sibling is born to be a donor for their sibling. This procedure, however, has been raising debate, especially concerning bioethics. Indonesia, a country with a high number of people who suffer from such an abnormal genetic condition, needs to be aware of this procedure and its policy framework. This paper conducts a comparative study in identifying and analyzing how saviour sibling is regulated in countries other than Indonesia. Besides, it discusses the legal and ethical implications of saviour sibling procedures in Indonesia. It is a cross-discipline research that combines legal research in the fields of health law, human rights law, and private law and resources from medical science. The analysis is established by using normative, comparative, and ethical approaches. This study found a disparity in the policy framework between countries because such a procedure is in the grey zone between bioethics and technologies. Nevertheless, no rights are violated because the child would live a life of physical and mental well-being. This procedure also plays a critical role in developing medical technology. In bioethics, the saviour sibling procedure begs whether the conceived sibling is just a means to an end, a mere commodity. In Indonesia, the legal framework on health technology involving human subjects is still relatively lax in regulating saviour siblings. Therefore, this study suggests that Indonesia needs to consider the diverse local wisdom as the foundation of its bioethics in regulating saviour sibling in the future.